2019
DOI: 10.3390/ijerph16061072
|View full text |Cite
|
Sign up to set email alerts
|

Does Sleep Mediate the Association between School Pressure, Physical Activity, Screen Time, and Psychological Symptoms in Early Adolescents? A 12-Country Study

Abstract: This study examines the mediating role of sleep duration and sleep onset difficulties in the association of school pressure, physical activity, and screen time with psychological symptoms in early adolescents. Data were retrieved from 49,403 children (13.7 ± 1.6 years old, 48.1% boys) from 12 countries participating in the World Health Organization (WHO) “Health Behaviour in School-aged Children” 2013/2014 study. A validated self-report questionnaire assessed psychological symptoms (feeling low, irritability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 45 publications
1
35
0
2
Order By: Relevance
“…In adolescent mental health, the effects of school pressure, physical activity, and mobile use time on psychological symptoms were mediated by sleep. 35 Furthermore, in our previous study, the effects of job stressors and social support on PPSR were also mediated by sleep. 20 Sleep problems play a mediating role in the association between occupational stress and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 80%
“…In adolescent mental health, the effects of school pressure, physical activity, and mobile use time on psychological symptoms were mediated by sleep. 35 Furthermore, in our previous study, the effects of job stressors and social support on PPSR were also mediated by sleep. 20 Sleep problems play a mediating role in the association between occupational stress and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 80%
“…In a study of 12 countries, it was found that school pressure and screen time were positively associated with psychological symptoms, whereas physical activity was negatively associated. Almost all associations were significantly mediated by sleep duration and sleep onset difficulties ( Vandendriessche et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review has shown that job stress increased the odds of insomnia . On the other hand, a recent study showed that sleeplessness is likely to mediate the association between school pressure and psychological symptoms . It is likely that a stressful environment can lead to sleeplessness and thus to further psychological problems when working with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Being physically active has been shown to reduce psychological symptoms in general . A Japanese study amongst dental students demonstrated that regular exercising was associated with lower stress levels .…”
Section: Discussionmentioning
confidence: 99%